Industrial Development Report 2016 - United Nations Industrial Development Organization (United Nations, 2015)
This report looks at how technology and innovation achieves inclusive and sustainable industrial development (ISID). Its main finding is that ISID is feasible and technology can simultaneously serve all three dimensions of sustainability, including economic, social and environmental. Rapid inclusive and sustainable industrialization can happen more frequently provided that policymakers firmly steer the industrialization process with opportune policies and avoid past mistakes. In some cases, the spread of technology has not materialized in concrete growth opportunities because of the lack of technological capabilities. Innovation needs to be supported by interventions strengthening the process from invention to adoption, as capabilities are developed and high tech manufacturing sectors are created, seeing higher rates of sustainable growth.